Halal industry’s organizational performance factors: a systematic literature review - Bidin, Rosmiza; Razak, Muhammad Nur Fitri; Mohamad, Bahtiar; Osman, Mohd Nizam; Abu Bakar, Mohd Syuhaidi; Tham, Jen Sern; Atan, Rodziah; Handayati, Puji; Utaberta, Nangkula (Universiti Putra Malaysia Press, 2021)
The global Halal industry is one of the world’s fastest-growing consumer segments, as evidenced by substantial research and published papers. This paper aims to identify and characterize the factors that influence organizational performance in companies within the Halal industry. It also offers an overview of the factors influencing companies’ organizational performance in various Halal industry sectors. A systematic Literature Review (SLR) of the Web of Science, Scopus, Emerald, and Science Direct databases guided by PRISMA (Preferred Reporting Items for Systematic Review and MetaAnalyses) protocol was used to analyze the data. The electronic database’s search results included articles focused on halal certification, halal product development, and supply chain management. A methodical review of these articles found four main factors that influence the organizational performance of halal companies: 1) the strategic management of Halal business, 2) the management of Halal requirements, 3) the understanding of consumer demands, and 4) the creation of the best organizational environment. This review provides detailed guidelines based on important research findings on how Halal organizations can manage and excel in their businesses. As a result, companies can better minimize the effect of volatile, uncertain, complex, and ambiguous (VUCA) environments in managing the business.